Mobile Application Clone Detection Using Digital Signature - Roslan, Emir Fikri; Abd Jalil, Kamarularifin (Applied Information Technology And Computer Science, 2024)
With the increased usage of mobile devices around the globe, the development of mobile apps has also increased. Application installs have increased proportion to the number of mobile devices usage. But with the increase of mobile applications installed on every user’s phone, not all are aware that they may be a victim of cybercrime. Some of the application has been cloned using reverse engineering and injected with custom codes with malware and virus. In this paper a method to detect mobile application clone using digital signature is proposed. This method works by sending data to the server to check for the original application signature and install application signature to verify if the application is safe to use. Hence the method of checking digital signature using Java method and using Java Native Interface that will call C/C++ library is implemented in order to avoid APK Signature Tampering.